2015
DOI: 10.2337/db15-0280
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes–Associated K+ Channel TALK-1 Modulates β-Cell Electrical Excitability, Second-Phase Insulin Secretion, and Glucose Homeostasis

Abstract: Two-pore domain K+ (K2P) channels play an important role in tuning β-cell glucose-stimulated insulin secretion (GSIS). The K2P channel TWIK-related alkaline pH-activated K2P (TALK)-1 is linked to type 2 diabetes risk through a coding sequence polymorphism (rs1535500); however, its physiological function has remained elusive. Here, we show that TALK-1 channels are expressed in mouse and human β-cells, where they serve as key regulators of electrical excitability and GSIS. We find that the rs1535500 polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(165 citation statements)
references
References 49 publications
3
162
0
Order By: Relevance
“…localization when tested in a mouse model (13). Our analysis revealed that rs1535500 is not associated with KCNK16 expression ( Fig.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…localization when tested in a mouse model (13). Our analysis revealed that rs1535500 is not associated with KCNK16 expression ( Fig.…”
Section: Significancementioning
confidence: 86%
“…Comparison of these maps with T2D GWAS SNPs has helped identify potential disease mechanisms. For example, the risk allele of the coding SNP rs1535500 has been implicated to increase KCNK16 activity and cell surface localization in a mouse model (13). Other risk alleles in SNPs in high LD with rs153550 are associated with increased expression of the neighboring potassium channel gene KCNK17, which is not in the mouse genome.…”
Section: Discussionmentioning
confidence: 99%
“…5-7 The nature of these oscillations depends on the proliferative, 8 developmental 9,10 and differentiated 11,12 state of the cell. Multiple animal models of diabetes have also demonstrated that the impaired insulin secretion characteristic of this disease, is due, in part, to dysfunctional Ca 2+ oscillations, 13-18 with studies on human β-cells corroborating this finding. 19-21 These Ca 2+ oscillations drive pulsatile insulin release 22 – a secretory pattern that enhances hepatic insulin action, 23 protects against insulin resistance, 24 and is lost in T2DM.…”
Section: Introductionmentioning
confidence: 84%
“…A KCNK16 SNP, rs1535500, has been identified in multiple T2DM GWAS [324][325][326]. Sitedirected mutagenesis of this SNP causing insertion of A277E into cloned human TALK-1 channels in mice resulted in increased surface localisation of TALK-1 and enhanced channel activity, which promoted beta cell membrane polarisation with resulting reduced calcium influx and reduced insulin secretion [323]. Thus this common variant results in a gain-of-function of TALK-1 and a reduction in insulin secretion.…”
Section: Chi Familiesmentioning
confidence: 99%
“…Thus this common variant results in a gain-of-function of TALK-1 and a reduction in insulin secretion. Conversely Kcnk16-deficient mice have beta cell membrane depolarisation, increased islet calcium influx and enhanced second phase (but not first phase) glucose-stimulated insulin secretion [323].…”
Section: Chi Familiesmentioning
confidence: 99%